2019
DOI: 10.1080/14790718.2019.1575837
|View full text |Cite
|
Sign up to set email alerts
|

The ordinary semiotic landscape of an unordinary place: spatiotemporal disjunctures in Incheon's Chinatown

Abstract: The ordinary semiotic landscape of an unordinary place: Spatiotemporal disjunctures in Incheon's Chinatown This article examines the semiotic landscape of the Chinatown in Incheon, South Korea. Using the geosemiotic framework as a heuristic guide, we analyze how the spectacle of Chinatown is constituted through spatial, linguistic, semiotic, and material resources, and find that the unordinariness of the place is contingent on and emerges through its juxtaposition with ordinary space, practice, and language us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For example, both Lou (2010Lou ( , 2016a and Leeman and Modan (2009) applied an analysis based on geosemiotics to the linguistic landscape of the Chinatown in Washington, DC (see also Chapter 3). Likewise, Lee and Lou (2019) examined the Chinatown of the city of Incheon in South Korea through the lens of geosemiotics, as did Zhao (2021) in Paris. Also drawing on geosemiotics, Xu and Wang (2021) focused on restaurants in a Chinatown in Sydney, combining their approach with Blommaert's (2013) ethnographic perspective.…”
Section: Chinatownsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both Lou (2010Lou ( , 2016a and Leeman and Modan (2009) applied an analysis based on geosemiotics to the linguistic landscape of the Chinatown in Washington, DC (see also Chapter 3). Likewise, Lee and Lou (2019) examined the Chinatown of the city of Incheon in South Korea through the lens of geosemiotics, as did Zhao (2021) in Paris. Also drawing on geosemiotics, Xu and Wang (2021) focused on restaurants in a Chinatown in Sydney, combining their approach with Blommaert's (2013) ethnographic perspective.…”
Section: Chinatownsmentioning
confidence: 99%
“…The authors concluded that adding the nighttime as a lens to linguistic landscape studies can offer valuable insights. Lee and Lou (2019) examined the reinvention of the Chinatown in the city of Incheon in South Korea. Overall, the authors observed that Korean was more frequently used than Chinese in the signage, but visually Chinese was more prominent.…”
Section: Chinatownsmentioning
confidence: 99%
“…Landry and Bourhis (1997) have defined signs as public road signs, public signs on government buildings, street names, place names, advertising billboards and commercial shop signs. The six types are categorised as 'top-down' and 'bottom-up' signs (Dixson, 2015;Fakhiroh & Rohmah, 2018;Landry & Bourhis, 1997;Lee & Lou, 2019). The former four types: public road signs, public signs on government buildings, street names, place names, can be defined as 'top-down signs', which means they are issued by national and public bureaucracy and public institutions.…”
Section: The Linguistic Landscape and Multilingualismmentioning
confidence: 99%
“…Linguistic landscape studies have shown how languages and semiotics co-construct the identities of people involved in the area and of the place (Gorter 2006;Pütz and Mundt 2018), making the interconnectivity and complexity of people, space, action, and language that comprise spatial identity visible (Benwell and Stokoe 2006). These studies tend to conclude that language and signs not only deliver information to be read by speakers of the language but also fulfil multiple purposes for which they are translingually used, including the construction of new meanings for existing language and space (Gorter and Cenoz 2015a; Lee and Lou 2019;Pennycook 2017). That is, existing language associated with a sign is given new meanings by how it is portrayed when consumed as part of a particular discourse by a certain group.…”
Section: Introductionmentioning
confidence: 99%